Amateur hour: Improving knowledge diversity in psychological and behavioral science by harnessing contributions from amateurs. (April 2022) - Mohlhenrich, Erik; Krpan, Dario
Abstract: Contemporary psychological and behavioral science suffers from a lack of diversity regarding the key intellectual activities that constitute it, including its theorizing, empirical approaches, and topics studied. We refer to this type of diversity as knowledge diversity. To fix the knowledge diversity problem, scientists have proposed several solutions that would require transforming the field itself—an endeavor that can realistically be realized only in the long term. In this article, we propose that knowledge diversity could also be attained in the short term without transforming the field itself—by harnessing contributions from amateurs who can explore diverse aspects of psychology that are neglected in academia. We identify six such "blind spot" areas within which amateurs could contribute and discuss how this could be practically achieved. We hope that our article will inspire professionals and academic institutions to be more open toward amateur contributions to create a diverse body of knowledge. Highlights: Low knowledge diversity is an important issue affecting psychological science. We propose this issue could be resolved by harnessing contributions from amateurs. We outline six "blind spots"—neglected areas in which amateurs could contribute. We discuss how amateur contributions could be practically achieved.